Efeito da terapia a laser de alta intensidade em pacientes com dor cervical crônica inespecífica - De la Barra Ortiz, Hernán Andrés (2024)
Chronic non-specific neck pain (CNNP) is a leading global cause of disability, affecting a significant portion of the population. Due to its multifactorial nature, which encompasses physical, psychosocial, and lifestyle factors, treatment requires comprehensive therapeutic approaches. Laser therapy has gained attention for its ability to alleviate pain and improve function in patients with musculoskeletal pain. While low-level laser therapy (LLLT) has demonstrated efficacy, high-intensity laser therapy (HILT) is emerging as a superior therapeutic option. HILT combines photobiomodulation with thermal effects, allowing for faster and more efficient energy delivery and covering larger treatment areas. This combination optimizes pain relief and tissue repair processes, offering a promising approach, particularly for pain resistant to conventional treatments. STUDY 1. A systematic review and meta-analysis of randomized controlled trials on the effectiveness of high-intensity laser therapy in the management of neck pain. Objective: The aim of this systematic review was to evaluate the effects of high-intensity laser therapy (HILT) on pain, disability, and range of motion in patients with neck pain. Methods: Randomized controlled trials (ECAs) on high-intensity laser therapy for neck pain disorders were searched across multiple databases, including PubMed, Web of Science, Scopus, CINAHL, Science Direct, Cochrane Library, the PEDro database, and Google Scholar (updated until January 7, 2024). Pain intensity was considered the primary outcome, while neck disability and range of motion were categorized as secondary outcomes. Researchers screened titles and abstracts using the Rayyan web application. Study quality was assessed using the Cochrane risk of bias tool, and evidence-based recommendations were formulated using the GRADE approach. A meta-analysis was conducted to calculate the pooled effect in terms of mean differences (MD) for the outcomes of interest, along with a 95% confidence interval (95% CI). Results: Twenty studies met the selection criteria and were considered potentially eligible for inclusion in the meta-analysis. At the end of treatment, a statistically significant pooled MD of -14.1 mm for pain intensity (17 ECAs) measured by the Visual Analog Scale (VAS) (95% CI: -18.4 to -9.7), 3.9° (95% CI: 1.9 to 6.7) for cervical extension (9 ECAs), and -8.3% (95% CI: -14.1 to -4.1) for disabilityreduction measured by the Neck DisabilityIndex (12 ECAs) was observed, all favoring HILT. Only the results for pain intensity aligned with the minimal clinically important differences (MCID) reported in the literature. Overall, the evidence was deemed significant but with low certainty, attributed to observed heterogeneity and some risk of bias among the ECAs. Conclusion: HILT demonstrates effectiveness in reducing neck pain and disability while enhancing cervical extension when combined with other physical therapy interventions, especially therapeutic exercises, based on a moderate level of evidence. This review highlights that the most favorable results are obtained when HILT is employed to address myofascial pain, cervical radiculopathy, and chronic neck pain. STUDY 2. Effect of high-intensity laser therapy in patients with nãon-specific chronic neck pain: study protocol for a randomized controlled trial Objective: The aim of this study is to present a protocol for a randomized controlled trial (ECA) that will assess the effect of high-intensity laser therapy (HILT) on pain intensity in patients with chronic nãon-specific neck pain (CNNP), considering the existing evidence on Low-level laser therapy (LLLT) for this condition. Methods: This is a two-arm randomized, placebo-controlled trial with blinded evaluators. The research will be conducted at the Electro-Physical Agents Laboratory of Andrés Bello University, Casona Campus, Santiago, Chile. Eligible participants will include members of the university's internal and external community who suffer from chronic, non-specific neck pain. Participants will be stratified by sex (four subgroups) and randomly assigned to one of two study groups: Group 1 (HILT and stretching exercises) or Group 2 (sham HILT and stretching exercises). Assessments will take place at three time points: before treatment (T0), immediately after treatment (T1), and 12 weeks after treatment completion (T2). Primary outcomes will include pain intensity at rest, pain intensity during active movements (flexion, extension, right and left side bending, and right and left rotation), and pain pressure threshold, calculated as the average across six evaluation points. Secondary outcomes will include neck range of motion in the sagittal, coronal, and transverse planes, as well as neck disability. Discussion: This study will compare the effects of HILT and a sham laser intervention on patients with CNNP. This ECA will provide new evidence regarding the potential benefits of HILT in terms of pain intensity, range of motion, and disability in individuals suffering from CNNP. The comparison with a control group will enable a more rigorous evaluation of HILT’s efficacy, contributing to the understanding of its clinical application and highlighting the need for evidence-based therapeutic approaches to manage this prevalent condition.